Divergence in Plant Traits and Increased Modularity Underlie Repeated Transitions Between Low and High Elevations in the Andean Genus Leucheria - Pérez, Fernanda; Lavandero, Nicolás; Ossa, Carmen Gloria; Hinojosa, Luis Felipe; Jara-Arancio, Paola; Arroyo, Mary T. Kalin (Frontiers in Plant Science, 2020)
Understanding why some plant lineages move from one climatic region to another is a mayor goal of evolutionary biology. In the southern Andes plant lineages that have migrated along mountain ranges tracking cold-humid climates coexist with lineages that have shifted repeatedly between warm-arid at low elevations and cold habitats at high elevations. Transitions between habitats might be facilitated by the acquisition of common traits favoring a resource-conservative strategy that copes with drought resulting from either low precipitation or extreme cold. Alternatively, transitions might be accompanied by phenotypic divergence and accelerated evolution of plant traits, which in turn may depend on the level of coordination among them. Reduced integration and evolution of traits in modules are expected to increase evolutionary rates of traits, allowing diversification in contrasting climates. To examine these hypotheses, we conducted a comparative study in the herbaceous genus Leucheria. We reconstructed ancestral habitat states using Maximum Likelihood and a previously published phylogeny. We performed a Phylogenetic Principal Components Analysis on traits, and then we tested the relationship between PC axes, habitat and climate using Phylogenetic Generalized Least Squares (PGLS). Finally, we compared the evolutionary rates of traits, and the levels of modularity among the three main Clades of Leucheria. Our results suggest that the genus originated at high elevations and later repeatedly colonized arid-semiarid shrublands and humid-forest at lower altitudes. PGLS analysis suggested that transitions between habitats were accompanied by shifts in plant strategies: cold habitats at high elevations favored the evolution of traits related to a conservative-resource strategy (thicker and dissected leaves, with high mass per area, and high biomass allocation to roots), whereas warm-arid habitats at lower altitudes favored traits related to an acquisitive-resource strategy. As expected, we detected higher levels of modularity in the clades that switched repeatedly between habitats, but higher modularity was not associated with accelerated rates of trait evolution.